Improving Color Recognition Ability Though Painting in Group B of TK One Roof Bulubete - Andriani, Nur; Said, Arsyad; Syamsidar, Syamsidar (Universitas Muhammadiyah Palu, 2021)
The research problem is children's ability to recognize color has not developed as expected. Â This aims to improve children's ability to recognize colors through painting. Subjects and research setting are 20 children of group B at TK Satu at Bulubete, consisting of 10 boys and ten girls registered in the 2019/2020 school year. This research uses Kemmis and Mc. Taggart design was carried out in cycles. The data collection technique is observation, assignment, and documentation, then analyzed descriptively. In pre-action data, the ability to mention color, BSH category is 10%, MB 15%, and BB 75%. The ability to show color, BSH category 10%, MB 20%, and BB 70%. The ability to group colors, category BSB 5%, BSH 15%, MB 15%, and BB 65%. After using the painting method, the child's ability to recognize color has increased from cycle I to cycle II. The BSB, BSH, and MB categories' ability to name color from 60% to 85% (25%). The ability to show the BSB, BSH, and MB categories colors from 55% to 85% (30%). The BSB, BSH, and MB categories' ability to group colors from 65% to 85% (20%). There is an increase in children's ability to recognize color from cycle I to cycle II with an average of 25% in the BSB, BSH, and MB categories and 15% of children in the BB category. The results of this research prove that the painting method can improve children's ability to recognize color in group B TK Satu Atap Bulubete.